COMPONENTS OF PUBLIC SPEAKING: THE FACTORS THAT MAKE STUDENTS INTERESTED IN ENGLISH SPEECH AND TEACHING - Muhammad - Sabri; Loly Novita (INOVISH JOURNAL, 2020)
Abstract: This study tries to find out which components of Public Speaking actually make the students interested in English speech and English teaching. This is a descriptive qualitative study where the data for the research were collected through a self-administered questionnaire distributed to all students of the fourth semester at English Study Program of State Polytechnic of Bengkalis â€“ Riau. Â The technique used to collect the data was done by asking the students to watch a video of a speech and then answer the questionnaire given. The questionnaire was set based on relevant literature review and also focused on condition of the students based on daily observation done by the writer during his teaching Public Speaking subject to the students. After collecting the data, the writer sorted the data by summarizing and choosing the specific category, displaying and verifying the data analysis and making the conclusion from the finding data. The findings of this research are hoped to give another point of view to English lecturers to realize certain parts of teaching that actually can make it more interesting for the students. The result of this study shows that Story Telling and Body Language performed by a speaker or a lecturer are among the most interesting aspects that make them interested in an English speech or teaching. Beside, this study also reveals that lack of Pauses and Visual Aids performed by the lecturers make their teaching become less interesting.